Is Support for Authoritarian Rule Contagious? Evidence from Field and Survey Experiments - Sirianne Dahlum; Torbjørn Hanson; Åshild Johnsen; Andreas Kotsadam; Alexander Wuttke (CESifo GmbH, 2024)
The increasing popularity of strongman rule in democratic societies underscores the need to explore how authoritarian regime preferences might spread socially. We assess the role of social influence on support for leaders with authoritarian inclinations through pre-registered field and survey experiments in the Norwegian Armed Forces. The field experiment randomly assigned soldiers to different rooms during boot camp, so soldiers lived among peers with varying levels of openness to authoritarian rule. We found that many individuals adjusted their privately reported support for authoritarian rule to align more closely with their peers. Further survey-experimental evidence among soldiers and the general Norwegian population confirms that learning about others' level of support for authoritarian rule changes both perceptions about the preferences of others' and own attitudes. Our results suggest that support for authoritarian rule can have a social basis and could potentially spread through social contagion in established democracies.
Keywords: D72; P00; J01; 330